Parental support in esports through the lens of the theory of planned behaviour - Svensson, Joar; Leis, Oliver; Trotter, Michael G. (Frontiers in Sports and Active Living, 2024)
Esports have grown substantially in the last decade and may be an effective way of engaging and exposing the youth, who is not actively participating in traditional sports, to the benefits of sports related performance environments. However, due to negative stereotypes about gamers and concerns about esports, parents might be hesitant to support their children's esports participation and may instead actively discourage it. The purpose of this perspective article was to discuss the determinants of parental support based on the theory of planned behaviour. Parents attitudes seem to be mostly negative and their perceived behavioral control is likely low due to a lack of knowledge about esports. The subjective norms are mixed and seem to be growing progressively more positive. Based on the theory of planned behaviour, parents seem unlikely to support their children's esport participation, however, more research is needed. Recommendations on how to increase the likelihood of parental support are discussed.